Pengaruh jumlah uang beredar dan tingkat suku bunga terhadap inflasi di indonesia tahun 1988 – 2017 - Nurul Hasinah; Arfiah Busari; Muliati Muliati (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2020)
This study aims to determine the effect of the money supply and interest rates to inflation in Indonesia in 1988-2017. The theory in this study uses the quantity theory of money which states that inflation can occur if there is an increase in the volume of the amount of money and the Gibson Paradox theory which explains that price trends and interest rates move together.This research was conducted using vector analysis tool Autoregression. The results of this study show that the money supply variables are statistically significant effect on the inflation and interest rate variables are statistically significant effect on inflation in Indonesia in 1988-2017 as evidenced by the Granger Causality test, Impulse Response Function and Variance Decomposition.